Early Modern Medicine in Manuscript and Print: A Triangulation Approach to Analysing Spelling Standardisation - Tyrkkö, Jukka (International Journal of English Studies, 2020)
The standardisation process of English spelling largely came to its conclusion during the Early Modern period. While the progress of standardisation has been studied in both printed and manuscript texts, few studies have looked at these processes side by side, especially focusing on the same genre of writing and by using corpora that are sufficiently large for quantitative comparison. Using two Early Modern medical corpora, one based on manuscripts and the other on printed sources, this paper compares the trajectories of spelling standardisation in the two textual domains and shows that while spelling standardisation progressed in an almost linear fashion in printed texts, the manuscripts reveal a much more varied and shallow cline toward standardisation.